Relación entre los medicamentos antiasmáticos y el desarrollo de caries dental en niños y adolescentes. Revisión sistemática (2021)
Antiasthmatic drugs contain components that can affect the oral cavity; which could be a risk factor for the development of dental caries. The objective of this study is to determine through the literature the relationship between antiasthmatic drugs and the development of dental caries in children and adolescents.